Learning from the Self-Created Media: Designing the Engineering Students’ ESP Autonomous Learning - Difiani Apriyanti; Sumira Sumira (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
Currently, English lecturers of non-English speaking countries in higher institutions are facing heterogeneous classes. There are fortunate students during their high schools who got a chance to sharpen their English skills and others who just rely on their English school teachers. Unaffordable costs or limited facilities or access to learning are some of the factors. The learning material of ESP for Engineering for a heterogeneous class is developed. This R&D used ADDIE approach. This article focuses on the analysis of the first two phases- analysis and design. Analysis of the need of the Engineering students and English lecturers are conducted using instruments of the open questionnaire and interview list which have been validated. While in the design phase, the material is developed using an autonomous learning approach and a task-based approach. Before, continuing to the practicality test, the developed material also has been validated. This material is aimed to support the learning of " Describing a Process" which is one of the topics in ESP in the Engineering Department of Politeknik Negeri Padang. The developed material provides every meaningful task that gives a positive contribution to the students.